Quantifying inherent safety of chemical process routes - Duncan Lawrence (1996)
Inherent safety is that which is intrinsic to a chemical plant. Chemical plants should be designed to be acceptably safe and it is better if this can be achieved through inherent safety, which can not be compromised, rather than engineered safety. The earlier that inherent safety is considered, the greater are the benefits. The choice of chemical route, that is the raw materials and the sequence of reactions that converts them to the desired products, is a key early design decision that influences the inherent safety of a plant. The inherent safety must be quantified in order to choose the optimum route from a number of alternatives. A trial inherent safety index has been developed for ranking alternative chemical routes by inherent safety. The physical properties of the chemicals involved, and the conditions in the reaction steps are parameters in the index calculation procedure. The index has been tested on a number of routes to methyl methacrylate (MMA). In order to verify and improve the index, a panel of experts was asked to rank the routes, and to make comments about the index and how it could be improved. This expert judgement exercise used three questionnaires and a group meeting to elicit the required information. Statistical methods were used to analyse the results from the questionnaires. The experts agreed closely among themselves on the rankings. The rankings from the trial index and the rankings from the experts matched closely. A new index was produced based on the comments of the experts and further research. The new index is more structured than the trial index, and separation and storage steps are included in addition to reaction steps. The inherent safety of the routes to MMA has been assessed with the new index. Developing a method for quantifying the inherent safety of chemical routes has proved to be a large and difficult task. Further research is needed to decide how the interactions between parameters affect the assessment of inherent safety. The ultimate goal is a computerised tool that could be used in the early stages of industrial process development.